STANDAR ISI MATERI PELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH (MTs) DALAM KURIKULUM 2013 (Tinjauan Psikologi Perkembangan) - Mujahid Mujahid (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2015)
This paper aims to review the content standard of the Arabic language subject in 2013 curriculum for MTs from the view of developmental psychology. On developmental psychology point of view, the content standard in Arabic subject for MTs some of them have accordance with the level of developmental psychology of students and others have not in accordance with the spirit development of learners. Arabic subject in MTs that has accordance with the development of learner thinking are still dominated by the concrete thought. In addition, the material is also in accordance with the emotional and moral development of students. However, if associated with a level of abstract thinking, the material is not yet supported, though adolescence developmental psychology should begin to be directed to abstract thinking. That incompatibility appears from the material that presents more concrete materials rather than abstract one.